Implementation of the ID3 Algorithm for Classification of Car Quality - Dimas Adi Putra Pratama; Nisvy Sya`'bana Nugraha; Risnandy Maulana; Adellia Rahmasari; Ahmad Fauzi (Gunung Djati Conference Series, 2021)
Transportation like a car is needed by most of family. Cheap, economical and comfortable family cars have been sold in the market. However, buyers must be careful in finding the car they want. To get the best car, many factors are taken into consideration, such as price, seating, and comfort. Comfort is the main thing in owning a car. There are cars that are expensive but do not have comfort, and vice versa. Therefore, we discuss how the Iterative Dichtomizer Three (ID3) Algorithm can be implemented for the classification process of any car with quality according to price, seat and passenger comfort.